Pollinators and pollination effects on three canola (Brassica napus L.) cultivars: A case study in Upper Egypt - Abdulraouf Mohamed Amro (Journal of King Saud University: Science, 2021)
This research aimed to survey the insect pollinators and visitors of canola, to assay their foraging activities and to study their effects on three canola cultivars (Pactol, Serw-4 and Serw-6) at the Experimental Field Station in Assiut region, Upper Egypt during two flowering seasons 2017/18 and 2018/19. The results manifested that there were nine species of insect pollinators and visitors belonging to four orders and eight families. The majority of the pollinators were Hymenoptera (83%), especially honey bees (Apis mellifera L.), Diptera (12%), Butterflies (Lepidoptera; 3%) and the beetles (Coleoptera; 2%). The peak activity of honey bees was recorded between 9 am and 11 am while for the other insect pollinators, except, syrphid flies was 11 am. The caged cultivars (without insect pollination) had statistically significant lower yield parameters (silique number per plant, seed number per silique, weight of 1000 seeds, oil content and seed germination) than the uncaged cultivars (accessible to insect pollinators and visitors). Uncaged plants of canola Pactol and Serw-4 cultivars had high seed oil content (44.34, 51.40%), seed yield (681.8, 429.0 kg/ha.) and seed germination percentage (80, 86%), respectively. Serw-4 cultivar had the first rank in the weight of siliques and seeds. This study indicated that the yield of the canola crop was positively influenced by insect pollinators. Serw-4 is a promising cultivar for large-scale production of edible oil.